Management systems and computers - Payne, Belinda P.; Modern business (New York : Alexander Hamilton Institute, 1968)
This book is designed to show how the office produces information which is meaningful to its management. It details the systems and procedures used to capture, store and retrieve the data concerning a company's operations.
Impact of the Computer. By William C. Norris. president Control Data Corporation. 28 p.
Includes bibliographical references and index.
hza 02/08/2018
Loans
Keywords: Electronic data processing; Office management; Office equipment and supplies